2014
DOI: 10.1016/j.bbrc.2014.06.085
|View full text |Cite
|
Sign up to set email alerts
|

Increased centrosome amplification in aged stem cells of the Drosophila midgut

Abstract: Age-related changes in long-lived tissue-resident stem cells may be tightly linked to aging and age-related diseases such as cancer. Centrosomes play key roles in cell proliferation, differentiation and migration. Supernumerary centrosomes are known to be an early event in tumorigenesis and senescence. However, the age-related changes of centrosome duplication in tissue-resident stem cells in vivo remain unknown. Here, using anti-γ-tubulin and anti-PH3, we analyzed mitotic intestinal stem cells with supernumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Hydrogen peroxide (Chae et al., 2005) and ROS-mediated autophagy (Pannu et al., 2012) are associated to centrosome amplification. Oxidative stress triggers centrosome amplification in Drosophila cells (Park et al., 2014a, Park et al., 2014b) and takes part in HeLa cells centrosome organization (Bollineni et al., 2014) and human centrin 2 radiolytical oxidation causes centrosome duplication abnormalities (Blouquit et al., 2007). The kDNA alteration of R72-treated parasites maybe caused by the oxidative stress, as the ROS-producing mitochondria are also affected by naphthoquinones (reviewed in Menna-Barreto and de Castro, 2014) and lapachone was shown to affect Crithidia fasciculata kinetoplasts (Biscardi et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide (Chae et al., 2005) and ROS-mediated autophagy (Pannu et al., 2012) are associated to centrosome amplification. Oxidative stress triggers centrosome amplification in Drosophila cells (Park et al., 2014a, Park et al., 2014b) and takes part in HeLa cells centrosome organization (Bollineni et al., 2014) and human centrin 2 radiolytical oxidation causes centrosome duplication abnormalities (Blouquit et al., 2007). The kDNA alteration of R72-treated parasites maybe caused by the oxidative stress, as the ROS-producing mitochondria are also affected by naphthoquinones (reviewed in Menna-Barreto and de Castro, 2014) and lapachone was shown to affect Crithidia fasciculata kinetoplasts (Biscardi et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The β-lapachone-mediated ROS production in a catalase-sensitive way triggers autophagic cancer cell death (Bey et al., 2013), as well as programmed necrosis or necroptosis in a mechanism involving receptor interacting protein (RIP)1, PARP-1 and apoptosis-inducing factor (AIF; Park et al., 2014a, Park et al., 2014b). In this regard, it is noteworthy that PARP activity was reported in all T. cruzi developmental stages (Fernández Villamil et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…If proven, the fact that abnormal centrosomes can drive malignant transformation by deregulating asymmetric cell division, an integral property of stem cells, could cause a paradigm shift. Increased centrosome amplification in aged and oxidatively stressed stem cells in the drosophila mid-gut and its link to polyploidy suggests the mechanism of propagating genome instability in older cells could be by modifying stem cell division in a centrosome dependent manner [53]. …”
Section: Discussionmentioning
confidence: 99%
“…ISCs are irregularly arrayed across the basement membrane and surrounded by ECs and visceral muscle [8]. Previous studies have revealed age-related phenotypes of ISCs; ISC hyper-proliferation, DNA damage accumulation, and increased centrosome amplification are associated with intestinal hyperplasia [12][13][14][15]. ISC homeostasis (the balance of proliferation and quiescence) has been known to be regulated by extrinsic factors such as cytokine ligands of Janus kinase (JAK)-signal transducer and activator of transcription (STAT), epidermal growth factor receptor (EGFR), and wingless signaling that are derived from niches, including EC, EB, EE, and visceral muscle [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%